Flexible Elliptical-Gradient Metallic Hollow Waveguide for 0.14 THz Delivery With Mode Tunable Properties - Zhao, Benlei; Pei, Xin; Jia, Yunjiang; Jiang, Jiachen; Zhu, Xiaosong; Shi, Yiwei (Journal of lightwave technology, 2025)
A flexible elliptical-gradient metallic hollow waveguide (EGMHW) is proposed, fabricated, and characterized. It is based on an elliptical-gradient polycarbonate (PC) base tube with inner silver film coating. The property of dynamical mode filtering from large to small port was theoretically analyzed and experimentally demonstrated, and it was tuned that only TE 11y remained at the small port. Nonreciprocally, the EGMHW has a relatively low straight transmission loss of 1.2 dB/m at operation frequency 0.14 THz from small to large port, compared to 5.3 dB/m of the inversed direction. This phenomenon and the loss characteristics for different bent angles and radii were analyzed in detail. Measured results show that the waveguide has a great polarization-maintaining performance with a polarization ratio of 99.4% as well as robustness for bending and twisting. Finally, the property of mode filtering was experimentally verified through imaging superposed field distribution of the remained mode and comparing with the corresponding numerical results. This work provides an effective way for the design of flexible low-loss mode-tunable THz waveguides.